Experimental Identification of the Void Fraction in a Large Hydrodynamic Offset Halves Bearing - Alexander Engels; Sören Wettmarshausen; Michael Stottrop; Thomas Hagemann; Christoph Weißbacher; Hubert Schwarze; Beate Bender (Lubricants)
A common approach to optimising hydrodynamic journal bearings for power loss is to reduce the lubricant supply and direct the oil to specific bearing areas where it is needed to guarantee safe operation. This requires information on the processes in the gap and the surrounding pocket areas for both pre-design and simulation. In this paper, a system consisting of a total of eight cameras is used to determine the void fraction in deep grooves outside the lubricant film. The void fraction in the lubrication gap is determined using a novel method for the evaluation of two proximity measurements. While the variation of the deep groove void fraction is realised by a special oil supply and radially adjustable deep groove elements, the gap void fraction is adjusted by the oil supply in the lube oil pockets at the pad leading edges. On the one hand, the experimental investigations show that the void fraction of the deep groove areas has hardly any influence on the general operating behaviour. On the other hand, the void fraction in the lubrication gap can be measured quantitatively for the first time, and the operating point-dependent gas fractions can be visualised. It is also shown that gaseous cavitation is the main mechanism in partially filled regions of the lubrication gap.